A política monetária na perspectiva pós-keynesiana - Deus, Larissa Naves de (2015)
This dissertation investigates the importance of monetary policy as a regulator of the monetary and financial system and as an automatic stabilization mechanism cycles of monetary economies of production, the way Keynes and the post-Keynesian perspective, which theoretically guide this work, define the capitalist economy. Specifically, this research answer the following questions: in view of the theoretical framework of Keynes and the progress made by the post-Keynesians authors, what could be the Keynesian monetary policy regime? What characteristics, mode of operation, instruments and institutions of AM? So there will be a theoretical research on the major works of Keynes dealing with the role of money and monetary policy, as well as the contributions made by post- Keynesian authors. The conclusions of the study conceive a Keynesian monetary regime consistent with the mode of operation of monetary economies of production in the AM seeks to address three objectives, listed hierarchically: full employment, monetary stability and financial stability. To achieve these objectives, has instruments for an active monetary policy, for the reserve requirements, rediscount rate, open market operations and financial regulatory measures. Furthermore, in relation to the institutions surrounding the AM, there is the freedom that it has to operate their instruments in pursuit of the goal of general economic policy outlined by the Government, and the importance of coordination between the economic policies for the proper functioning Keynesian monetary regime.